Pink Cricket Balls Through Rose-Tinted Glasses: Enhancing Interceptive Timing. (November 2017) - Adie, Joshua M.; Arnold, Derek H.
Cricket is a popular but potentially dangerous sport. It is played with a hard ball that can travel at great speeds. Serious injuries, including fatalities, have occurred when balls have struck participants. The game is traditionally played during daylight with a dark red ball, but recent games have been played during the day and at night using a 'pink' ball. We have reported data that seemed to justify concerns raised regarding the visibility of these new pink balls, as they were revealed to have a very low luminance contrast against pertinent backgrounds during twilight. Here, we report on the findings of a psychophysical experiment, wherein we mimicked twilight lighting conditions in an interceptive timing experiment using a pink moving disc as an analogue for pink cricket balls. We show that interceptive timing performance is diminished in conditions that mimic twilight. More importantly, we show that wearing glasses with a rose-tinted filter can alleviate this adverse impact by enhancing the luminance contrast of the pink 'ball' relative to pertinent backgrounds.